(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
With the progression of HIV infection, opportunistic infections join. A special place in the structure of opportunistic infections is occupied by herpesvirus infections, which manifest themselves in an immunodeficient state with various clinical, manifestations, affecting many organs and tissues, worsening the quality of life of HIV- infected patients.